Analysis of the Effect of Workload, Motivation, and Job Satisfaction on Employee Performance (Study at Indomie Food Stalls in Solo Raya) - Muchammad Reza Pahlevy; Farid Wajdi (Majapahit Journal of Islamic Finance and Management, 2026)
This study investigates the influence of workload, motivation, and job satisfaction on employee performance in Indomie food stalls across the Solo Raya region. Employing a quantitative research design, the study translates abstract concepts into measurable indicators, enabling precise empirical analysis of the relationships among the variables. Workload is defined as the mental and physical demands placed on employees, motivation as the internal drive to achieve objectives, and job satisfaction as positive emotional responses to work experiences. Data were collected through purposive sampling of active employees using validated Likert-scale questionnaires, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that motivation and job satisfaction significantly and positively affect employee performance, while workload shows a negative but non-significant effect. Despite providing valuable insights, the model explains only 36.2% of the variance in employee performance, suggesting additional factors such as leadership style, work environment, or discipline may influence outcomes. Future research is recommended to broaden the study context, incorporate additional variables, and refine measurement instruments, particularly for workload, to better capture the dynamics of informal culinary work environments.